Low-Carbon Investment and Credit Rationing - Christian Haas; Karol Kempa (Environmental and Resource Economics, 2023)
This paper develops a principal-agent model with adverse selection to analyse firms' decisions between an existing carbon-intensive technology and a new low-carbon technology requiring an externally funded initial investment. We find that a Pigouvian emission tax alone may result in credit rationing and under-investment in low-carbon technologies. Combining the Pigouvian tax with interest subsidies or loan guarantees resolves credit rationing and yields a first-best outcome. An emission tax set above the Pigouvian level can also resolve credit rationing and, in some cases, yields a first-best outcome. If a carbon price is (politically) not feasible, intervention on the credit market alone can promote low-carbon development. However, such a policy yields a second-best outcome. The issue of credit rationing is temporary if the risks of low-carbon technologies decline. However, there are social costs of delay if credit rationing is not addressed.
Keywords: G20; H23; H81; Q50; 330; Asymmetric information; Credit rationing; Emission tax; Interest rate subsidy; Loan guarantee; Low-carbon investment